Intrapulmonary lymph node (stations 13 and 14) metastasis in peripheral non-small cell lung cancer. Issue 27 (9th July 2021) - Bi, Lei; Zhang, Hong; Ge, Mingjian; Lv, Zhongzhu; Deng, Yiping; Rong, Tenghao; Liu, Chaolun
Abstract : Abstract: It remains unknown whether dissecting the intrapulmonary lymph nodes (stations 13 and 14) when resecting peripheral non-small cell lung cancer (NSCLC) is necessary for accurate tumor node metastasis (TNM) staging. This study investigated intrapulmonary lymph node dissection (stations 13 and 14) on the pathological staging of peripheral NSCLC and the metastatic pattern of the lymph nodes. This retrospective study included patients with primary peripheral NSCLC who underwent radical dissection between January 2013 and December 2015. The clinical data of patients and examination results of intrapulmonary stations 12, 13, and 14 lymph nodes were analyzed. Of 3019 resected lymph nodes in a total of 234 patients (12.9/patient), 263 (8.7%) had metastasis. Ninety-nine patients had lymph node metastasis (42.3%): 40 (17.1%) were N1, 11 (4.7%) were N2, 48 (20.5%) were both N1 and N2, and 135 (57.7%) had no N1 or N2 metastasis. Sixteen (6.8%) patients had metastasis of stations 13 and/or 14. Metastasis in N1 positive patients of stations 10, 11, 12, 13, and 14 were 2.7%, 10.5%, 9.8%, 10.4%, and 8.5%, respectively. Missed detection without station 13 and 14 dissection was up to 6.8% (16/234). Dissection of stations 13 and 14 could be helpful for the identification of lymph node metastasis and for the accurate TNM staging of primary NSCLC.